Effect of Adding Polypropylene Plastic Waste on Compressive Strength and Flexural Strength Concrete - Fadila, Tiara; Khotimah, Sucianti Husnul; Sudarsono , Ignatius (CIVED, 2024)
Indonesia is the second largest producer of plastic waste in the world after China with an annual contribution of 187.2 million tons of plastic waste. This study aims to analyze the effect of the addition of plastic seeds with polypropylene substitution on the compressive strength and flexural strength of concrete with the intention of reducing waste waste and utilizing it as a concrete mixing material and making concrete properties into green concrete. The method used is the experimental method by making several variations of concrete mixtures with plastic seeds of polypropylene type as a substitute for part of the sand. The mixing of plastic seeds is divided into several variations, namely, 3% polypropylene seeds and 6% polypropylene seeds. Analysis of the test results of the addition of polypropylene seeds compared to the concrete mixture without polypropylene seeds resulted in a compressive strength of 24.14 MPa for the addition of 3%, as well as a value of 23.25 MPa for the addition of 6% each at 28 days of concrete age. As for the flexural strength, an increase value of 0.16 MPa was obtained for the addition of 6% and the addition of 3% at the age of 28 days. This study shows that the results of the study have reached the planned quality target, namely the quality of fc'20 Mpa.